STRATEGI PEMASARAN SEPEDA MOTOR PREMIUM HONDA PADA PT ENAM TIGA SEJAHTERA - Felieani Setiabudi (Agora, 2018)
This research was conducted to develop competitive strategy at PT Enam Tiga Sejahtera. This research uses qualitative descriptive research method. To determinate the interviewees the method that has been use is purposive sampling technique. Then the validity of the data is tested by using source triangulation method. Application of intensive strategy is the most appropriate approach can be used by the companies to face the competition. Market development strategies are run by marketing and selling premium motorcycle products in the new territories that do not have Honda wing dealers. The results of this study indicate that the appropriate strategy for PT Enam Tiga Sejahtera is market development